Planetary analog sites in the Indian subcontinent and the Indian Ocean: underexplored environments suited for astrobiological and space research - Jangir, Yamini; Dutta, Subham (Frontiers in Astronomy and Space Sciences, 2026)
Astrobiology seeks to understand the origin, evolution, distribution, and future of life in the Universe, focusing on habitability beyond Earth. Due to the high cost and complexity of space missions, studying planetary analog sites on Earth is essential for supporting and de-risking future exploration. These analog sites are extreme terrestrial environments that mirror environmental, geological, geochemical, or biological conditions on other planetary bodies. Investigating how life persists in these settings advances knowledge of extraterrestrial habitability and enables realistic testing of life-detection instruments. This review presents the first comprehensive synthesis of more than 50 planetary analog field sites across the Indian subcontinent and Indian Ocean region. We identify 2 geological regions with active astrobiological research, 4 requiring targeted geochemical and geomicrobiological surveys, and 5 with high planetary relevance but minimal study. We assess how these sites fill gaps in global astrobiological research and evaluate their readiness for future investigations. The sites include high-altitude cryospheric settings such as Himalayan glaciers and permafrost, analogues to Martian and lunar environments; saline-alkaline lakes like Sambhar Lake, comparable to Martian paleolakes; intrabasaltic bole beds in the Deccan Traps, relevant to phyllosilicate formation on Mars; subsurface caves and mines, analogous to lunar lava tubes; and hydrothermal vent systems along the Central and Southwest Indian Ridges, relevant to icy ocean worlds. Comparing these sites to global analogues reveals that, although most are not yet fully characterized, several offer unique environmental combinations. As deep-space missions prepare to search for life beyond Earth, a geographically broader set of analog sites is critical. Highlighting the diversity and scientific value of these under-characterized regions in South Asia and their marine periphery, this review provides a foundation for characterizing previously overlooked planetary analog sites. These sites expand the global analogue parameter space and offer underutilized natural laboratories for planetary habitability and biosignature research.